Peluang dan Intervensi Pengembangan Desa Wisata Potensi Wisata Bahari di Kabupaten Serang. - Allyreza, Rahmawati; Rahmi Winangsih; Winangsih, Rahmi (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
Village Tourism is currently a prima donna destination to release fatigue and find a new atmosphere in traveling. Especially with the covid-19 pandemic, the level of tourist visits to tourist villages has increased dramatically. Wargasara Tourism Village on Tunda Island is a tourist village in Serang Regency which has maritime potential. Wargasara Tourism Village on Tunda Island has great potential to be developed but experiences obstacles related to infrastructure facilities, understanding of tourism by the community, weak local government support. To overcome these obstacles, an analysis of opportunities and interventions in the development of Wargasara tourism village with marine potential is needed. The research method used is qualitative with literature review (using references to springer, science direct and scopus articles) and in-depth interviews with objective informants. This research provides another picture of the opportunities and interventions for the development of tourist villages with marine potential from the study of public administration using the dimensions of governance, namely institutions, values and processes. Improving and strengthening the governance of Wargasara tourism village is expected to answer the challenges faced in maximizing the potential of marine tourism in Serang Regency.